THE SUCROSE LEVEL’S DIFFERENCES OF PACKAGED DATES AND BULK PURCHASING DATES THROUGH IODOMETRI LUFF SCHROOL METHODS - Indah Lestari; Christ Kartika Rahayuningsih; Aprilia Irmawati (poltekkes kemenkes mataram, 2016)
Abstract: Fruits, vegetables and honey contain a high sucrose, when digested (hydrolyze), sucrose will be seperated into glucose and fructose. Chemically, sugar level on dates consists of sucrose, glucose and fructose. Basically, food packaged aims to maintain the quality of freshness, giving simplicity of storage and distribution. Above all, it can reduce the air contamination, water, and soil. Therefore, the purpose in this research was to find out the differences of sucrose level on packaged dates and bulk purchasing dates. This study was a comparative quantitative analysis technique using iodometry method with Luff Schrool to each 4 sample of packaged dates and bulk purchasing dates which were chosen selectively at the Ampel Surabaya market with sample criteria, packaged dates with no brand and bulk purchasing dates in plastic. From the samples analyzed, sucrose concentration obtained was average 9.73% of packaged dates and bulk purchasing dates was14.45%. The analysis results with normality test and T test two indipendent samples can be concluded that there were differences between the sucrose level of packaged dates and bulk purchasing dates. People should consume bulk purchasing dates due to it can be used as an alternative solution to obtain higher substitute energy than packaged dates, it is caused by sucrose level on bulk purchasing dates is higher.